1998
DOI: 10.1159/000017934
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose Narrow-Band UVB Phototherapy Combined with Topical Therapy Is Effective in Psoriasis and Does Not Inhibit Systemic T-Cell Activation

Abstract: Background: Psoriasis is a chronic T-cell-mediated inflammatory skin disease which can be treated with topical medication, phototherapy or systemic medication. A subgroup of psoriatic patients does not respond to monotherapy and needs combination therapy. We used low-dose narrow-band UVB phototherapy, combined with balneotherapy, short-contact anthralin, liquor carbonis detergens and calcipotriol for treatment of psoriatic patients in our day care centre. Objective: Our purpose was to study the efficacy, induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…There are several solutions to this perceived disadvantage, however. One is that psoriasis clears with less aggressive NB‐UVB regimens that do not lead to erythema 9,18,54,55 . Treatment times have been shortened in many studies without sacrificing efficacy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several solutions to this perceived disadvantage, however. One is that psoriasis clears with less aggressive NB‐UVB regimens that do not lead to erythema 9,18,54,55 . Treatment times have been shortened in many studies without sacrificing efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…Physicians should consider that, as NB‐UVB seems to clear psoriasis faster, it should theoretically require fewer treatments, thus compensating partially for the longer treatment times. Finally, it is important to keep in mind that combining NB‐UVB with other modalities, such as tazarotene gel, 56 anthralin, 57 and calcipotriol, 58,59 or even day treatment, 55 can provide faster, more effective, clearance and a reduction in the mean number of treatment sessions and cumulative irradiation doses. Using lower doses of light and additional treatments with complementary modes of action may also minimize side‐effects, such as unpredictable erythema and lesion blistering.…”
Section: Discussionmentioning
confidence: 99%
“…De Rie, et al found that sIL2R levels were well correlated with disease activity in patients with PV and closely followed the decrease of disease activity during immunosuppressive therapy (22). Duncan et al revealed that serum levels of sIL2R decreased after treatment with PUVA (psoralen-UVA) and Cyclosporine therapy, but did not change with NB-UVB (narrow-band UVB) treatment (23,24).…”
Section: Psychological Resultsmentioning
confidence: 99%
“…As the levels of sIL‐2R does not correlate well with Sézary cell and CD25 + blood lymphocyte counts, most of the sIL‐2R appears to be derived from neoplastic cells in the skin or lymph nodes rather than from circulating cells 4 . It is also reported that the levels of sIL‐2R is elevated in patients with psoriasis, but NB‐UVB does not suppress the elevated levels 5 . It is possible that sIL‐2R is released from circulating T cells in patients of psoriasis.…”
Section: Casementioning
confidence: 99%